1992
DOI: 10.1159/000173452
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol Infusion Increases the Maximal Tubular Capacity of Phosphate Reabsorption

Abstract: Isoproterenol, a β-adrenoreceptor agonist, decreases urinary phosphate (Pi) excretion; however, plasma phosphate concentration also decreases. The purpose of the present study was to determine the effect of isoproterenol infusion on phosphate reabsorption with concomitant phosphate infusions and in the presence and absence of parathyroid hormone (PTH). Clearance experiments were performed on male Sprague-Dawley rats which were acutely thyroparathyroidectomized (TPTX) and successive infusions of phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The procedure for this experiment was modified from methods of addition, recent studies in humans [8] and mice [9] with Mü hlbauer et al [4], LeClaire et al [12], and Thornton et al [16]. Eight XLH have found that there are mutations in the PEX treatment groups (four doses ¶two genotypes) were studied with gene, renamed PHEX [10] ( phosphate-regulating gene approximately 10 animals per group.…”
Section: Tmp Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…The procedure for this experiment was modified from methods of addition, recent studies in humans [8] and mice [9] with Mü hlbauer et al [4], LeClaire et al [12], and Thornton et al [16]. Eight XLH have found that there are mutations in the PEX treatment groups (four doses ¶two genotypes) were studied with gene, renamed PHEX [10] ( phosphate-regulating gene approximately 10 animals per group.…”
Section: Tmp Measurementmentioning
confidence: 99%
“…Then constant levels of 3 H-inulin (0.09 Ci/h) and isoproterenol of phosphate in male Sprague-Dawley rats [12,13]. -(0.0, 0.25, 0.5, or 1.0 g/kg/min) were infused at 0.6 ml/h throughout Adrenoreceptors responded to -adrenergic agonists and the remainder of the experiment.…”
Section: Tmp Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, there is no precise information about PTH activity in severe infection. In our previous studies, the renal response to endotoxin (Et) administration was found to be resistant to the phosphaturic effect of PTH [7]; hormonal and blood neutrality alterations, such as an increased norepinephrine excretion, hypocapnia, and metabolic acidosis were observed in these previous studies, and all of these responses inhibit the phosphaturic effect of PTH [9][10][11][12][13][14], in particular the first two factors do it by enhancing renal nerve activity. We, therefore, hypothesized that enhanced renal nerve activity during endotoxemia is responsible for the observed hypophosphaturia.…”
Section: Phosphatementioning
confidence: 99%